2021
DOI: 10.1021/acsami.0c22011
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of Peptide–Chondroitin Sulfate Nanoparticles Allows Efficient Photoprotection in Skin

Abstract: In this article, we describe a method of delivery of chondroitin sulfate to skin as nanoparticles and demonstrate its anti-inflammatory and antioxidant role using UV irradiation as a model condition. These nanoparticles, formed through electrostatic interactions of chondroitin sulfate with a skin-penetrating peptide, were found to be homogenous with positive surface charges and stable at physiological and acidic pH under certain conditions. They were able to enter into the human keratinocyte cell line (HaCaT),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…To effectively treat neovascular AMD, the nanocarriers must be able to transport drugs into the retina, especially into the RPE. Among various approaches under investigation to enhance drug bioavailability in the retina, exploitation of cell penetrating peptides (CPPs) is the most recent and promising advancement; noting that cell uptakes of both drugs and nanocarriers can be significantly improved when incorporated with CPPs. Furthermore, CPPs have been proved to be favorable in promoting absorption of macromolecules through different tissues such as the skin, the intestine, the nasal mucosa, and ocular tissues. Inspired by these findings, it is hypothesized that the development of nanotherapeutics capable of synchronously delivering both resveratrol and metformin (as model hydrophobic and hydrophilic drugs, respectively) into the retina, via harnessing the retinal penetration of CPPs and tailorable structures of PCL, can lead to an effective treatment of neovascular AMD.…”
mentioning
confidence: 99%
“…To effectively treat neovascular AMD, the nanocarriers must be able to transport drugs into the retina, especially into the RPE. Among various approaches under investigation to enhance drug bioavailability in the retina, exploitation of cell penetrating peptides (CPPs) is the most recent and promising advancement; noting that cell uptakes of both drugs and nanocarriers can be significantly improved when incorporated with CPPs. Furthermore, CPPs have been proved to be favorable in promoting absorption of macromolecules through different tissues such as the skin, the intestine, the nasal mucosa, and ocular tissues. Inspired by these findings, it is hypothesized that the development of nanotherapeutics capable of synchronously delivering both resveratrol and metformin (as model hydrophobic and hydrophilic drugs, respectively) into the retina, via harnessing the retinal penetration of CPPs and tailorable structures of PCL, can lead to an effective treatment of neovascular AMD.…”
mentioning
confidence: 99%
“…The inhibitory activities of CVP on neurotransmitter release and melanin synthesis proved its potential as a safe and active cosmeceutical ingredient with antiwrinkle and skin-whitening effects. M9, a skin-penetrating peptide, was employed to deliver chondroitin sulfate (CS), which has anti-inflammatory and antioxidant effects . A topical delivery of the nanoparticles formed through electrostatic interactions of CS with M9 provided protection for the skin against UV-B radiation with negligible toxic effects on keratinocytes.…”
Section: Action Modes Of Cpp-mediated Transdermal Delivery In the Skinmentioning
confidence: 99%
“…Thus, instead of utilizing injections or abrasive processes, a completely non-invasive technique was used to introduce biomolecules within the skin. 109 Over the years, although substantial efforts have led to the discovery of proteins, drugs, and polypeptides to prevent growth, neovascularization, and metastasis of tumors, several peptides suffer from short half-life and low stability, and a lack of targeted delivery. To overcome these drawbacks, Xing L. et al prepared a novel CS-ES2-AF peptide NP conjugate (as demonstrated in Fig.…”
Section: Wistar Ratsmentioning
confidence: 99%
“…Thus, instead of utilizing injections or abrasive processes, a completely non-invasive technique was used to introduce biomolecules within the skin. 109…”
Section: Recent Advances In Cs-based Formulations In Biomedical Appli...mentioning
confidence: 99%